Long-term use of antibiotics and risk of colorectal adenoma. Issue 4 (4th April 2017) - Cao, Yin; Wu, Kana; Mehta, Raaj; Drew, David A; Song, Mingyang; Lochhead, Paul; Nguyen, Long H; Izard, Jacques; Fuchs, Charles S; Garrett, Wendy S; Huttenhower, Curtis; Ogino, Shuji; et al.
Abstract : Objective: Recent evidence suggests that antibiotic use, which alters the gut microbiome, is associated with an increased risk of colorectal cancer. However, the association between antibiotic use and risk of colorectal adenoma, the precursor for the majority of colorectal cancers, has not been investigated. Design: We prospectively evaluated the association between antibiotic use at age 20–39 and 40–59 (assessed in 2004) and recent antibiotic use (assessed in 2008) with risk of subsequent colorectal adenoma among 16 642 women aged ≥60 enrolled in the Nurses' Health Study who underwent at least one colonoscopy through 2010. We used multivariate logistic regression to calculate ORs and 95% CIs. Results: We documented 1195 cases of adenoma. Increasing duration of antibiotic use at age 20–39 (ptrend =0.002) and 40–59 (ptrend =0.001) was significantly associated with an increased risk of colorectal adenoma. Compared with non-users, women who used antibiotics for ≥2 months between age 20 and 39 had a multivariable OR of 1.36 (95% CI 1.03 to 1.79). Women who used ≥2 months of antibiotics between age 40 and 59 had a multivariable OR of 1.69 (95% CI 1.24 to 2.31). The associations were similar for low-risk versus high-risk adenomas (size ≥1 cm, or with tubulovillous/villous histology, or ≥3 detected lesions), but appeared modestly stronger for proximal compared with distal adenomas. In contrast, recent antibiotic use within the past four years was not associated with risk of adenoma (ptrend =0.44). Conclusions: Long-term antibiotic use in early-to-middle adulthood was associated with increased risk of colorectal adenoma.